A2.3 STAT3-regulated gene expression in circulating CD4+ T cells discriminates RA patients independently of clinical parameters in early arthritis: a validation study. (13th February 2015) - Pratt, AG; Anderson, AE; Diboll, J; Nair, N; Skelton, A; Lendrem, D; Hargreaves, B; Routledge, C; Brown, P; Stocks, P; Barton, A; Isaacs, JD
Abstract : Background and objectives: We previously identified a 12-gene "signature, " enriched for STAT3 target genes, which was predictive of rheumatoid arthritis (RA) in circulating CD4 + T cells of early arthritis patients. We conducted an independent replication study, and interpreted its findings in the context of other clinically relevant baseline parameters. Materials and methods: Gene expression in highly purified peripheral blood CD4 + T cells from disease modifying anti-rheumatic drug (DMARD)- and steroid-naïve patients with suspected inflammatory arthritis was measured using Illumina microarray technology. A nested analysis focussed on normalised expression of those transcripts hybridised by the 12 probes identified during the previous study. Concurrent STAT3 pathway activation was determined in CD4 + T cells by paired whole blood flow cytometry, and detailed clinical and serological data were recorded for all participants. Analyses included the use of univariate tests, hierarchical clustering and logistic regression. Results: In this independent cohort of 161 early arthritis patients, normalised expression of ten out of the 12 CD4 + T cell "signature" genes studied differed significantly between patients presenting with RA and alternative diagnoses (p < 0.05). Hierarchical clustering using the signature discriminated an RA-enriched subgroup of early arthritis patients. Differential expression was most pronounced for the STAT3-regulated genes PIM1, BCL-3 and SOCS3 (>1.3-fold difference; p < 0.001 in each case), each of whose expression correlated strongly with paired CD4 + T cell intracellular phospho-STAT3. Multivariate analysis confirmed that the expression of each of these three genes predicted a diagnosis of RA independently of CRP, ESR, swollen joint count and age. Conclusions: The regulation of gene expression by STAT3 in circulating CD4 + T cells is confirmed as an early event in RA pathogenesis. The functional relevance of this observation remains the subject of on-going in vitro investigation.